2016
DOI: 10.1371/journal.pone.0167839
|View full text |Cite
|
Sign up to set email alerts
|

Fast Dissemination of New HIV-1 CRF02/A1 Recombinants in Pakistan

Abstract: A number of HIV-1 subtypes are identified in Pakistan by characterization of partial viral gene sequences. Little is known whether new recombinants are generated and how they disseminate since whole genome sequences for these viruses have not been characterized. Near full-length genome (NFLG) sequences were obtained by amplifying two overlapping half genomes or next generation sequencing from 34 HIV-1-infected individuals in Pakistan. Phylogenetic tree analysis showed that the newly characterized sequences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
6
18
1
Order By: Relevance
“…In another study, population density and frequent migration of HIV-infected individuals have been suggested to influence the emergence of novel subtypes or inter-subtype recombinants and circulating recombinant forms [37,38]. The findings of the current study are in agreement with a previous study conducted in Sindh province, Pakistan, in which multiple HIV-1 subtypes and inter-subtype recombinants were identified [15,[39][40][41]. Furthermore, according to the Los Alamos HIV Database, subtype A (74.2%) is the most frequently reported HIV-1 subtype in Pakistan, while subtype B, C, G, A1/G, 02_AG, 35_AD, 02A1, 01_AE and others account for 5.7%, 4.3%, 1.6% and 1.7%, 4.3%, 1.4%, 2.7%, 2.9% and 1.3%, respectively (www.hiv.lanl.gov).…”
supporting
confidence: 91%
“…In another study, population density and frequent migration of HIV-infected individuals have been suggested to influence the emergence of novel subtypes or inter-subtype recombinants and circulating recombinant forms [37,38]. The findings of the current study are in agreement with a previous study conducted in Sindh province, Pakistan, in which multiple HIV-1 subtypes and inter-subtype recombinants were identified [15,[39][40][41]. Furthermore, according to the Los Alamos HIV Database, subtype A (74.2%) is the most frequently reported HIV-1 subtype in Pakistan, while subtype B, C, G, A1/G, 02_AG, 35_AD, 02A1, 01_AE and others account for 5.7%, 4.3%, 1.6% and 1.7%, 4.3%, 1.4%, 2.7%, 2.9% and 1.3%, respectively (www.hiv.lanl.gov).…”
supporting
confidence: 91%
“…CRF01_AE has spread widely through sexual transmission among MSMs. The significantly higher percentage of recombinants in this study than those previously reported [4,8,9] demonstrates that the proportion of recombinants in a region can be significantly underestimated using only partial genome sequences [31][32][33][34]. An accurate distribution of HIV-1 subtypes, CRFs and unique recombinants can only be reliably estimated by NFLG sequences.…”
Section: Discussioncontrasting
confidence: 46%
“…Recently, Chen et al . [ 10 ] reported on unique CRF02_AG/A1 recombinants, indicating ongoing recombination between locally transmitted CRF02_AG and A1 strains, suggesting that these unique recombinants may become major epidemic strains in Pakistan. It is likely that we underestimated the proportion of recombinant HIV-1 sequences in our population given we only sequenced a portion of the HIV-1 pol gene.…”
Section: Discussionmentioning
confidence: 99%
“…The observed 20-30% amplification failure was likely due to nucleic acid degradation during storage [8] and/or low viral loads (≦ 1,000 copies/mL) [9]. Even though our HIV-1 genotyping primers have been validated in-house as part of the Canadian HIV-1 Strain and Drug Resistance Surveillance program, we cannot rule out the possibility of amplification failure attributed to poor primer annealing efficiency to sequences from unique HIV-1 circulating recombinant forms (CRFs) recently reported in Pakistan [10].…”
Section: Serology Amplification and Sequencingmentioning
confidence: 98%